Incidence and association of TCF7, TCF7L2 single nucleotide polymorphisms in type 1 diabetes mellitus patients of South Tamil Nadu, India - Velayutham, Kumaravel; Ramanathan, Balaji; Selvan, Sivan Arul; Gomathinayagam, Rohini (International Journal Of Community Medicine And Public Health, 2019)
Background: The TCF family genes TCF7 (T cell specific transcription factor-7) and TCF7L2 (transcription factor 7 like 2) are increasingly recognized to play a pivotal role in the incidence, pathophysiology of type 1 diabetes mellitus (T1DM). However, the prevalence and the influence of these allelic variants in the Indian/south Indian T1DM population is completely obscure. Methods: Genomic DNA was isolated from the peripheral blood samples of healthy controls, T1DM patients, and PCR (polymerase chain reaction), restriction fragment length polymorphism (RFLP), allele specific PCR (ASP), PCR product sequencing strategies were utilized to determine the prevalence of the TCF7 (exon 3, flanking intron 2, 3 regions) and TCF7L2 (intron 4) polymorphisms. Clinical investigations included assessment of the blood glucose/ estimated average glucose levels (EAG) and C-peptide levels. Results: The results indicate that 34.9% and 3.17% of the T1DM patients harbored the TCF7L2 rs7903146 and the TCF7 rs386692598 polymorphisms, respectively. Assessment of biochemical parameters indicated that the rs7903146 positive T1DM patients exhibited significantly lower EAG levels (p<0.05), suggesting that these patients may exhibit phenotypic heterogeneity, a milder disease course. The study further demonstrates that PCR based strategies enable reliable molecular diagnosis of T1DM in small scale diagnostic units. Conclusions: T1DM patients from south Tamil Nadu present TCF7, TCF7L2 genetic variations and screening for these polymorphisms will empower physicians to provide appropriate therapy and genetic counselling.